Acute Mesentric Venous Thrombosis with a History Recurrent DVT in Young Age: A Case Report - Z. A. Haldis; B. A. Kuncoro (MEDICINUS, 2020)
Acute mesenteric ischemia (AMI) may be defined as a sudden interruption of the blood supply to a segment of the small intestine, leading to ischemia, cellular damage, intestinal necrosis, and eventually patient death if left untreated. Mesenteric venous thrombosis (MVT) is an emergency condition that is rarely found as a cause of AMI compared to arterial thrombosis, and accounts for only 16% of all mesenteric ischemia cases. The overall incidence is low (0.09-0.2% of all acute admissions to emergency department), prompt diagnostic and intervention are essential in order to reduce the high mortality rate (50-80%).